The Future of Food Waste - LCA of existing and emerging routes to bio-based chemicals - Carlsson, Erica (My University, 2016)
There are large quantities of food waste to handle in society. Food waste can be used as a renewable feedstock to produce bio-based platform chemicals such as succinic acid. The goal of this thesis is to compare the environmental impact of three options for food waste management and/or production of bio-based succinic acid. These options were production of biogas from food waste, production of succinic acid from food waste and production of succinic acid from corn. The aim was to evaluate which of these options is the preferred one from an environmental point of view when it comes to managing food waste respectively producing bio-based succinic acid. A cradle-to-gate Life Cycle Assessment (LCA) of the production of biogas and succinic acid from food waste was performed. The results were compared to published LCA results of succinic acid production from corn. The results show that production of biogas is an environmentally better option for food waste management than production of succinic acid. If food waste or corn is the best feedstock to use for succinic acid production from an environmental point of view depends on the modelling choices. When no impact from food production was included and mass allocation was used, food waste was a better option than corn. If economic or no allocation was used or if the impact from food production was included, corn was a better option than food waste. Besides the used allocation method and inclusion of emissions from food production, the impact results were also affected by the assumed yield in the recovery process for succinic acid and the enzyme use. The results of this study show that the environmental impacts of producing succinic acid from food waste and corn are in the same range. This can be seen as a motivation to proceed with further environmental investigations.
Keywords: Hållbar utveckling; Annan naturvetenskap; Sustainable Development; Other Natural Sciences